Effect of custom design insole applications with 3D modelling on baropodometric parameters in individuals with pes planus - Aydoğan, Özgür; Yazıcı, Naile Hande; Tarakçı, Devrim; Atılgan, Esra (Nevzat Demirci, 2023)
It was aimed to investigate the effect of custom made insoles on baropodometric analysis parameters in individuals with pes planus, using objective measurement and production methods. 100 individuals with pes planus, aged between 4-18 years in the study. Individuals who met the inclusion criteria and the medial longitudinal arch index were included in the study. Valgus angles of individuals, plantar measurements of the feet before the use of insoles and after 6 months of the use of insoles were evaluated with the Sensor Medica® device. When the measurement results of the ankle valgus angles of the individuals before and after the insoles were examined, it was observed that there was a statistical decrease in the mean results in both feet (p[removed].
Keywords: 3D Design; Foot; Insole; Pes Planus; Plantar Pressure